Several Mode-Locked Pulses Generation and Transmission over Soliton Based Optical Transmission Link - IS Amiri; SE Alavi (Institute of Advanced Engineering and Science, 2016)
A soliton-based optical communication system is presented to generate and transmits several mode locked laser pulses (generated by fiber laser setup) over 50 km fiber and 120 m wireless link. The passive mode-locking feature of the laser system proposed in this paper is based on nonlinear polarization rotation evolution.